Papillary thyroid cancer with translocation in the TPM3‑NTRK1 gene - M. R. Savchuk; N. V. Shved; N. A. Savelov; I. L. Plaksa (Опухоли головы и шеи)
The study objective – to identify specific morphological criteria characteristic of papillary thyroid cancer with translocations in the NTRK genes.Materials and methods. A retrospective analysis of 130 cases of morphologically confirmed papillary thyroid cancer from the archives of the Moscow City Oncology Hospital No 62, Moscow Healthсare Department was performed. The morphological selection criteria for the immunohistochemical study were: metastatic lesions of the lymph nodes, microcalcifications, extrathyroid spread of the tumor, the presence of a capsule / intratumorous areas of connective tissue, invasion (into the tumor capsule, blood vessels, lymphatic vessels), the presence of intranuclear pseudo-inclusions, the follicle quantity <5 %. Thus, all criteria of thyroid cancer with detected translocation in NTRK genes found in the literature were used. If the tumor met the criteria we performed an immunohistochemistry study with Ventana pan-TRK (EPR17341) Assay antibodies was performed on a BenchMark Ultra immunoassayer. In case of a positive immunohistochemistry reaction, next-generation sequencing on the Illumina HiSeq high-throughput genome-wide sequencing system.Results. Of the 130 cases analyzed, we identified 10 cases of tumor with histological features characteristic of NTRK positive thyroid cancer. In all cases, the disease was characterized by an indolent course, a slow increase in the tumor over a long time. In patient 5, a tumor of the thyroid gland was combined with extra-organ sarcoma of the retroperitoneal space. The sizes of the tumor node varied from 0.5 . 0.5 cm to 4.0 . 3.0 cm. All patients had metastases to the lymph nodes, in 3 cases the tumor grew beyond the thyroid capsule. According to the results of an immunohistochemical study with antibodies to NTRK (out of 10 applicants) mutation was detected in 1 case. Cytoplasmic expression of varying severity was observed in 95 % of tumor cells. TPM3‑NTRK1 translocation was confirmed by next-generation sequencing.Conclusion. The presented study demonstrates the possibility of using morphological criteria for detecting thyroid tumors with mutations in the NTRK genes. In the case of a larger sample, it will be possible to identify the structural features of tumors with NTRK mutations. This will clarify morphological criteria and increase the probability of detecting a mutation, which is essential when choosing treatment methods (prescribing targeted therapy).